2021
DOI: 10.3390/ijms222312659
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Analysis of IL-23A- and/or EBI3-Including Cytokines Produced by Psoriatic Keratinocytes

Abstract: Interleukin (IL) 23 (p19/p40) plays a critical role in the pathogenesis of psoriasis and is upregulated in psoriasis skin lesions. In clinical practice, anti-IL-23Ap19 antibodies are highly effective against psoriasis. IL-39 (p19/ Epstein-Barr virus-induced (EBI) 3), a newly discovered cytokine in 2015, shares the p19 subunit with IL-23. Anti-IL-23Ap19 antibodies may bind to IL-39; also, the cytokine may contribute to the pathogenesis of psoriasis. To investigate IL23Ap19- and/or EBI3-including cytokines in ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The interleulin-12 cytokine IL-39 is known to mediate inflammatory response and is implicated in immunopathogenesis of diseases such as psoriasis (17), systemic lupus erythematosus (4), myocardial infarction (18) and hepatocyte necrosis (19). This study indicated an increased level of IL-39 in RA patients (G1-G3) compared to healthy control assuming significance as results show that IL-39 probably contributes to inflammatory response in RA as seen in other disease studied.…”
Section: Discussionsupporting
confidence: 50%
“…The interleulin-12 cytokine IL-39 is known to mediate inflammatory response and is implicated in immunopathogenesis of diseases such as psoriasis (17), systemic lupus erythematosus (4), myocardial infarction (18) and hepatocyte necrosis (19). This study indicated an increased level of IL-39 in RA patients (G1-G3) compared to healthy control assuming significance as results show that IL-39 probably contributes to inflammatory response in RA as seen in other disease studied.…”
Section: Discussionsupporting
confidence: 50%
“…Quantitative analysis showed a significant increase in epidermal thickness in HFD-fed Apoe −/− mice (Figure 2d). Exacerbated inflammatory skin changes in the HFD-fed Apoe −/− mice were confirmed by the increased expression of IL-23p19, signal transducer and activator of transcription-3 (STAT3), and phospho-STAT3 in the epidermis of inflamed skin (Figure S1), which are known to be activated in psoriatic skin [19,20]. Collectively, these data indicate that the combination of obesity and dyslipidemia triggered more intense psoriatic inflammation than obesity or dyslipidemia alone.…”
Section: High-fat-diet-induced Obesity and Apoe-deficiency-induced Dy...mentioning
confidence: 75%
“…15 However, increasing evidence shows that neutrophils are the most abundant cell type producing IL-17 in psoriatic lesions. 27,28 Studies have demonstrated that IL-23 can specifically promote the transcription-level production of IL-17A, IL-17F, and IL-22 by neutrophils. IL-23 induces to produce IL-17 through the STAT3-dependent RoRγt and BATF pathways by neutrophil.…”
Section: Il-17 Produced By Neutrophilsmentioning
confidence: 99%
“…90 Among them, LL-37 is recognized as the main autoantigen of psoriasis, 91 which ultimately induces Th17 cells to produce IL-17 92 through a series of reactions. Increasing evidence shows that KCs can produce IL-23, 19,28,93 triggering a cascade reaction (Figure 1). One of the pathways leading to the release of IL-23 by KCs is the activation of TLR3, which can be dependent on double-stranded RNA (dsRNA).…”
Section: The Interaction Of Neutrophils With Other Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation